2016
DOI: 10.1051/e3sconf/20160710002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of vulnerability to storm induced flood hazard along diverse coastline settings

Abstract: Abstract. European coasts suffer notably from hazards caused by low-probability and high-impact hydrometeorological events. The aim of the study is to assess in probabilistic terms the magnitude of stormǦinduced flooding hazard along Varna regional coast (Bulgaria, western Black Sea) and to identify susceptible coastal sectors (hotspots). The study is performed employing the Coastal Risk Assessment Framework (CRAF) developed within EU FP7 RISC-KIT project. It constitutes a screening process that allows estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…After application of the empirical models on regional scale, obtained extreme hazard series of TWLs and shoreline retreats were subjected to Extreme Value Analysis (Valchev et al 2016) and hazard intensities relevant to return periods of 20, 50 and 100 years were determined. Further in the process of hazard assessment, flooding hazard extents were determined using the "bathtub" approach or calculated through the overwash extent formulations (eq.…”
Section: Hazard Intensities and Extentsmentioning
confidence: 99%
“…After application of the empirical models on regional scale, obtained extreme hazard series of TWLs and shoreline retreats were subjected to Extreme Value Analysis (Valchev et al 2016) and hazard intensities relevant to return periods of 20, 50 and 100 years were determined. Further in the process of hazard assessment, flooding hazard extents were determined using the "bathtub" approach or calculated through the overwash extent formulations (eq.…”
Section: Hazard Intensities and Extentsmentioning
confidence: 99%
“…The process is described in (Eftimova et al 2017). Subsequently, the calculated TWLs were best fitted to Generalized Extreme Value distribution (Valchev et al 2016). Hazard intensities relevant to return periods of 20, 50 and 100 years were further analyzed since they were considered benchmark values by most of the regional stakeholders.…”
Section: Hazard Assessment Backgroundmentioning
confidence: 99%
“…Ultimately, the CRAF approach combines several hazard and exposure indicators into a single index, thereby allowing a rapid comparison of coastal sectors. Results on application of the framework and identification of 'hotspots' along Varna regional coast are presented in Valchev et al (2016), while the present study mainly focuses on and presents results of assessment of receptors' exposure vulnerability.…”
Section: Introductionmentioning
confidence: 99%
“…The selected hotspot -a highly vulnerable coastal sector according to Valchev et al (2016) includes Varna beach and the breakwater of Port of Varna (herein referred to as port wall) ( Fig. 2).…”
Section: Study Sitementioning
confidence: 99%
“…Therefore, main data source was a wave hindcast dataset spanning 63-year period (1949-2012) (Valchev et al 2012). In compliance with thresholds set in Valchev et al (2016), more than 140 individual events were identified each represented by maximum significant wave height (Hs), corresponding peak wave period (Tp), mean wave direction and storm duration. As for peak surge level (h), the historic component of data originating from another modeling study (Vousdoukas et al 2016) was considered.…”
Section: Compilation Of Synthetic Datasetmentioning
confidence: 99%